Learning Organization Intervention In Social Co-Workers, Innovative Behaviors, Work Environments And Influence On Work Engagement In Supervisors (Study At Pt. Acs Surabaya) - Hepiyanto; Arif Hidayat (Institute of Computer Science (IOCS), 2022)
Having an engaged supervisor is a great asset to the organization, this trait requires a learning process in the organization that is supported by mutually supportive, innovative behavior and a conducive work environment. For this reason, this study aims to measure the influence of social co-workers, innovative behavior, and work environment on work engagement with learning organizations as ab intervening variable. This study took a sampling technique with a total population study or saturated sample of 68 employees at the Supervisor level at PT. ACS Surabaya, and data analysis are carried out using a path analysis model. The results of the study obtained the value of t = 6.545; p = 0.000 (p <0.05), which means that social co-workers have a positive and significant effect on the supervisor’s work engagement; innovative behavior has a positive and significant effect on the supervisor work engagement with a value of t=3.120 and p=0.027 (p<0.05); Social co-workers have a positive effect on work engagement intervened by supervisor learning organization with a value of t = 5.134 with p = 0.000 (p <0.05); Innovative behavior has a positive effect on work engagement which is intervened by supervisor learning organization with a value of t = 2.782 and p = 0.007 (p <0.05). While the work environment factors either directly or intervened by the learning organization did not affect the work engagement of the supervisors at PT. ACS Surabaya.